2023
DOI: 10.1055/a-2007-1893
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Adipose Tissue Insulin Resistance and Diabetic Parameters in Drug Naïve Subjects with Type 2 Diabetes Treated with Canagliflozin Monotherapy

Abstract: The objective of this study is to investigate the link between the baseline/changes of body weight and those of diabetic parameters during treatment with an SGLT-2 inhibitor. Drug naïve subjects with T2DM received canagliflozin monotherapy for 3 months. Adipo-IR was selected as the significant factor responsible for the changes of (Δ)BMI with this drug. While no correlations were noted between ΔBMI and ΔFBG, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 28 publications
0
0
0
Order By: Relevance
“…HOMA-R exceeding 2.5 generally signifies the presence of insulin resistance [ 10 , 15 ], while HOMA-B below 30% indicates low beta-cell function [ 10 , 15 ]. Obesity is defined as BMI above 25 [ 8 ]. Considering these contextual factors, it is postulated that newly diagnosed, untreated Japanese patients with T2DM exhibit characteristics of high insulin resistance, relatively preserved beta-cell function, modest overweight status, and poor glycemic control.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…HOMA-R exceeding 2.5 generally signifies the presence of insulin resistance [ 10 , 15 ], while HOMA-B below 30% indicates low beta-cell function [ 10 , 15 ]. Obesity is defined as BMI above 25 [ 8 ]. Considering these contextual factors, it is postulated that newly diagnosed, untreated Japanese patients with T2DM exhibit characteristics of high insulin resistance, relatively preserved beta-cell function, modest overweight status, and poor glycemic control.…”
Section: Discussionmentioning
confidence: 99%
“…SGLT-2 inhibitors reduce both weight and insulin resistance. However, previous findings have suggested that specific populations treated with SGLT-2 inhibitors may not experience weight loss, and correlations between changes in insulin resistance and weight are not consistently observed [ 8 ]. A TZD drug, such as pioglitazone, reduces insulin resistance but contributes to weight gain [ 4 , 6 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations